2015
DOI: 10.1016/j.pestbp.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Locomotory and physiological responses induced by clove and cinnamon essential oils in the maize weevil Sitophilus zeamais

Abstract: Plant essential oils have been suggested as a suitable alternative for controlling stored pests worldwide. However, very little is known about the physiological or behavioral responses induced by these compounds in insect populations that are resistant to traditional insecticides. Thus, this investigation evaluated the toxicity (including the impacts on population growth) as well as the locomotory and respiratory responses induced by clove, Syzygium aromaticum L., and cinnamon, Cinnamomum zeylanicum L., essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 72 publications
(32 citation statements)
references
References 64 publications
1
31
0
Order By: Relevance
“…Respiratory rate and body mass of insects can represent the sum of the energy demands of the physiological processes of insects that are necessary to produce defense mechanisms against the essential oils and toxic compounds495051. Thus, low respiration rate is an indicator of physiological stress, and essential oils can compromise insect respiration by impairing muscle activity, leading to paralysis495051. Several studies of plant volatile and their constituents were shown to effectively disrupt the recognition process of the host substrate and influence the walking behavior on insects5253.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory rate and body mass of insects can represent the sum of the energy demands of the physiological processes of insects that are necessary to produce defense mechanisms against the essential oils and toxic compounds495051. Thus, low respiration rate is an indicator of physiological stress, and essential oils can compromise insect respiration by impairing muscle activity, leading to paralysis495051. Several studies of plant volatile and their constituents were shown to effectively disrupt the recognition process of the host substrate and influence the walking behavior on insects5253.…”
Section: Discussionmentioning
confidence: 99%
“…Imidacloprid has distinct pharmacological profiles in diverse subtypes of insect nAChRs [ 34 38 ]. Furthermore, such alterations in walking behavior has been shown to be a strategy used by insects to overcome the actions of natural and synthetic insecticides [ 19 , 29 , 48 50 , 52 ]. Such higher walking activity in exposed males of E .…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral bioassays were conducted in arenas that were fully treated either with imidacloprid residues (at 0.042 μg a.i./cm 2 , the equivalent of 1% of the field rate dose), or with deionized water (control), following methods previously described elsewhere [ 48 52 ]. Briefly, the filter paper disks were impregnated with 1 mL of insecticide or water solution and, after drying for 20 min, the filter paper was placed in Petri dishes (135 × 20 mm).…”
Section: Methodsmentioning
confidence: 99%
“…Notably, short‐term exposure to deltamethrin did not affect the swimming activity of M. bentoi or B. tarsalis as a group, which might be the result of a less intense insecticide poisoning per individual. With backswimmers, individual swimming activity is reduced as the density increases , and in general, reduced locomotor activity is apparently a strategy widely used by insects to mitigate the effects of insecticide toxicity .…”
Section: Discussionmentioning
confidence: 99%